Ricoeurian Hermeneutics and Indian Thought: Analyzing Evil in Cross-Cultural Philosophy - Bilimoria, Puruṣottama (Sophia, 2025)
This paper examines the intersection of Western and Indian hermeneutical traditions, focusing on Paul Ricoeur's hermeneutics and its application to the Upaniṣads. Engaging with the broader hermeneutical debates between Gadamer, Habermas, and Ricoeur, the study highlights the tensions between tradition and critical reflection. Ricoeur's "hermeneutics of suspicion" is employed to interrogate dominant interpretations shaped by the Brahmasūtra, particularly those that prioritize mokṣa (liberation) as the central goal of the Upaniṣads. Drawing from the Mīmāṃsā tradition and Nirukta exegesis, the study introduces a "decolonial hermeneutics of trust," which reframes these texts in terms of embodied experience rather than transcendence. Through an analysis of Upaniṣadic doctrines and myths, particularly the struggles between deva-s and asura-s, the paper explores the concept of pāpmā/pāpman (‘evil’) as an amoral force of privation that affects perception and disrupts the unity of the self. By bridging Western philosophical discourse, focusing on Ricoeur's work, with Indian hermeneutical methods, this study reveals the cross-cultural dimensions of meaning-making while also challenging essentialist readings of Indian thought. The philosophical investigation contibutes to a broader rethinking of hermeneutical frameworks, emphasizing the dynamic interplay between critique and tradition in interpreting classical texts.